Beyond detection and correction: Fake news’ «news-ness» and «shareworthiness» as alternative ways to tackle disinformation - Raúl Rodríguez-Ferrándiz (Communication & Society (Formerly Comunicación y Sociedad))
Fake news is a concern for present-day society. A lot of quality research efforts have focused on how fake news can be detected, and to what extent general warnings, accuracy prompts and fact-checking labels can correct people’s misconceptions. In this work we problematize critically the research questions formulated on fakeness detection and specifically we address two significant alternative (though complementary) approaches: 1) What formal traits and news values do fake news best imitate, which sheds light on what “news” means (irrespective of falsity) since the rise of social media as news source (news-ness assessment), and 2) what factors explain fake news sharing (shareworthiness prediction), which explains why it is shared with a higher intensity than real news, even in the case of awareness that a falsity is being shared. Intertwined with these approaches, two theories compete to best explain fake news’ social pervasiveness and virality: the ignorance theory (aptitudes: be mistaken, confused or careless about assessing news accuracy, resulting in sharing falsehoods unintentionally) and the partisan theory (attitudes: motivated reasoning and political bias which encourages people to knowingly share fake news consistent with their view). The aim is twofold: to identify, compare and challenge the scholars’ underlying assumptions and practical implications, and to draw a coherent narrative that encompasses the motivation to deceive, the social media affordances that make this deception plausible and shareable, and the polarization, intergroup hostility, and the greater exposure to extreme political views that may boost disinformation.